Efficacy and safety of sintilimab plus XELOX as a neoadjuvant regimen in patients with locally advanced gastric cancer: A single-arm, open-label, phase II trial - Guo, Honghai; Ding, Ping’an; Sun, Chenyu; Yang, Peigang; Tian, Yuan; Liu, Yang; Lowe, Scott; Bentley, Rachel; Li, Yaru; Zhang, Zhidong; Wang, Dong; Li, Yong; et al. (Frontiers in Oncology, 2022)
Background Neoadjuvant chemotherapies have been widely recommended in patients with locally advanced gastric cancer (LAGC). However, the evidence of combining neoadjuvant chemotherapy with anti–programmed death 1 (anti–PD-1) antibody therapy for patients with LAGC is lacking. Thus, we conducted a single-arm phase II trial to evaluate the efficacy and safety of the anti–PD-1 antibody sintilimab plus XELOX regimen (capecitabine plus oxaliplatin) in patients with LAGC. Methods Patients with LAGC (cT3-4 N+ M0, CY0, P0) were enrolled and received four preoperative cycles of sintilimab (200 mg, IV, Q21d) plus XELOX (oxaliplatin 130 mg/m2, IV, d1 with capecitabine 1,000 mg/m2, bid, d1–d14, Q21d) therapy. The primary endpoint was the pathological complete response (pCR) rate. This clinical trial was registered at Chictr.org.cn (trial number: ChiCTR2000030414). Results Thirty patients were enrolled from March 2020 to July 2021, with a median age of 62 years (range, 30–72), and 18 (60.0%) were men. There were 19 (63.3%) patients with PD-L1 CPS ≥1.The pCR rate was 33.3% [95% confidence interval (CI), 17.3%–52.8%], and the major pathologic response (MPR) rate was 63.3% (95% CI, 43.9%–80.1%). All the patients underwent R0 resection. The objective response rate (ORR) and the disease control rate (DCR) were 70.0% (95% CI, 50.6%–85.3%) and 100% (95% CI, 88.4%–100%), respectively. Downstaging of the overall TNM stage was observed in 22 (73.3%) patients. The pCR rate in patients with PD-L1 CPS ≥1 and patients with PD-L1 CPS <1 was 42.1% vs. 18.2% (P = 0.246), whereas the MPR rate was 78.9% vs. 36.4% (P = 0.047). The potential immune-related adverse events (irAEs) were hypothyroidism (3.3%), pneumonia (10.0%), and dermatitis (6.7%). Grade3 common treatment-related adverse events (TRAEs) were ALT increase (3.3%), AST increase (3.3%), and dermatitis (3.3%) during the neoadjuvant therapy. There were no severe complications or death related to the surgery. Conclusion Sintilimab plus XELOX as neoadjuvant therapy showed an encouraging pCR rate, MPR rate, and manageable safety. This combination of regimens might provide a new option for patients with LAGC. Clinical Trial Registration: Chictr.org.cn, identifier ChiCTR2000030414.